Dr. Vladas Ingelevičius activity of Lithuanian Red cross during German occupation - Stanionytė-Zujienė, Gražina (Genocidas ir rezistencija, 2002)
Dr Vladas Ingelevičius – the most prominent official of the Lithuanian Red Cross (LRC), who served on the Society’s board from its foundation (12 January 1919) to the second Soviet occupation (July 1944), with a break of six years (1932–1938) which was in protest against the interference of the Ministry of the Interior of Lithuania in the Society’s activities. In 1938, he was appointed Vice–Chairman of the LRC by President Antanas Smetona; Dr Vladas Ingelevičius was also the head of the Society and the work of its institutions during the German occupation (1941–1944), being the de facto fifth chairman of the LRC